Boosting Ambient Hydrogen Storage in Graphene via Structural and Functional Designs: A Review - Shun Wang; Chaojie Liu; Yongyang Zhu (Advanced Energy & Sustainability Research)
Graphene with a large specific surface area, excellent mechanical flexibility, and chemical adjustability is a promising medium for reversible hydrogen storage. The hydrogen adsorption capacity predicted for graphene under ideal conditions of low temperature and high pressure reaches 6.6 wt%, but the practical capacity at ambient conditions is far away from the theoretical value, mainly blamed on the weak Van der Waals interaction between hydrogen and graphene. In this case, strategies including structural engineering and functional modification have been widely adopted to create more adsorption active sites for hydrogen molecules and enhance their binding strength. Herein, the sustainable progress for enhancing the ambient hydrogen storage ability of graphene from both structural and functional perspectives is reviewed, with their synergy especially focused. Moreover, each strategy is further classified and discussed based on the difference of specific action mechanisms, with representative works introduced, aiming to presenting a clear and comprehensive development venation to the reader. Lastly, future research directions for developing advanced graphene‐based hydrogen storage systems are proposed.